IL-33 signaling is essential to attenuate viral-induced encephalitis development by downregulating iNOS expression in the central nervous system. Issue 1 (December 2016) - Franca, Rafael; Costa, Renata; Silva, Jaqueline; Peres, Raphael; Mendonça, Leila; Colón, David; Alves-Filho, José; Cunha, Fernando
Abstract Background Viral encephalitis is a common cause of lethal infections in humans, and several different viruses are documented to be responsible. Rocio virus is a flavivirus that causes a severe lethal encephalitis syndrome in humans and also mice, providing an interesting model to study the CNS compartmentalized immune response. Interleukin 33 (IL-33), a member of the IL-1 family, is an immunomodulatory cytokine that is highly expressed in the CNS. However, the role of IL-33 on viral encephalitis remains unclear. Therefore, we aimed to explore how the IL-33/ST2 axis regulates the local immune response during Rocio virus infection. Methods Wild-type (WT), ST2 (ST2−/− ), and nitric oxide synthase-deficient mice (iNOS−/− ) and Stat6 (Stat6−/− )-deficient mice were infected with different concentrations of the Rocio virus by intraperitoneal route, the cytokine mRNA level in CNS was analyzed by qPCR, and cellular immunophenotyping was performed on infected mice by the flow cytometry of isolated CNS mononuclear cells. Results We have shown that the mRNA expression of IL-33 and ST2 receptors is increased in the CNS of Rocio virus-infected WT mice and that ST2−/− mice showed increased susceptibility to infection. ST2 deficiency was correlated with increased tissue pathology, cellular infiltration, and tumor necrosis factor alpha (TNF-α) and interferon-gamma (IFN-γ) mRNA levels and higher viral load in the CNS, compared with wild-type mice. The increased Th1 cytokine levels released in the CNS acted on infiltrating macrophages, as evidenced by flow cytometry characterization of cellular infiltrates, inducing the expression of iNOS, contributing to brain injury. Moreover, iNOS−/− mice were more resistant to Rocio virus encephalitis, presenting a lower clinical score and reduced mortality rate, despite the increased tissue pathology. Conclusions We provide evidences of a specific role for IL-33 receptor signaling in nitric oxide induction through local IFN-γ modulation, suggesting that nitric oxide overproduction might have an important role in the progression of experimental viral encephalitis.